Perfluorooctane sulfonate (PFOS) affects hormone receptor activity, steroidogenesis, and expression of endocrine‐related genes in vitro and in vivo. (27th December 2012) - Du, Guizhen; Hu, Jialei; Huang, Hongyu; Qin, Yufeng; Han, Xiumei; Wu, Di; Song, Ling; Xia, Yankai; Wang, Xinru
Abstract Perfluorooctane sulfonate (PFOS) is a widespread and persistent chemical in the environment. We investigated the endocrine‐disrupting effects of PFOS using a combination of in vitro and in vivo assays. Reporter gene assays were used to detect receptor‐mediated (anti‐)estrogenic, (anti‐)androgenic, and (anti‐)thyroid hormone activities. The effect of PFOS on steroidogenesis was assessed both at hormone levels in the supernatant and at expression levels of hormone‐induced genes in the H295R cell. A zebrafish‐based short‐term screening method was developed to detect the effect of PFOS on endocrine function in vivo. The results indicate that PFOS can act as an estrogen receptor agonist and thyroid hormone receptor antagonist. Exposure to PFOS decreased supernatant testosterone (T), increased estradiol (E2) concentrations in H295R cell medium and altered the expression of several genes involved in steroidogenesis. In addition, PFOS increased early thyroid development gene (hhex and pax8) expression in a concentration‐dependent manner, decreased steroidogenic enzyme gene (CYP17, CYP19a, CYP19b) expression, and changed the expression pattern of estrogen receptor production genes (esr1, esr2b) after 500 µg/L PFOS treatment in zebrafish embryos. These results indicate that PFOS has the ability to act as an endocrine disruptor both in vitro and in vivo by disrupting the function of nuclear hormone receptors, interfering with steroidogenesis, and altering the expression of endocrine‐related genes in zebrafish embryo. Environ. Toxicol. Chem. 2013;32:353–360. © 2012 SETAC